Learners skills affected by the integration of local potential in biology: A review study - Ezif Rizqi Imtihana; Djukri Djukri (Universitas Ahmad Dahlan, 2020)
Integration of local potential in biology is important as a form of learning that is more contextual and brings students closer to the object the reality of life. The purpose of this research review is to examine the kinds of Indonesian local potential that are integrated in biology learning according to the biology topic raised so it will be known how the effect to students skills. This research is a review analysis following 4 steps. 21 articles were selected from 33 article published in the last 5 years (2015-2019). Eligibility of the 21 selected journals was checked through expert judgement based on criteria. The research article were searched using the Educational Resources Information Center (ERIC), Sinta Indonesia, and Google Scholar online database. The results of the analysis show that the kinds of local potentials integrated in biology are natural resources, simple technology, and the surrounding environment. Biology topics that apply the integration of local potential in biology are the environment, ecosystem, biodiversity, and plant structure. The integration of local potential in biology affects 5 students skills, that are literacy skills, science process skills, generic skills, thinking skills, and science attitude skills. The effect size results show that the effect of integration of local potential is greatest on generic skills with the big category, while other skills experience significant fluctuations. The results of this review can be followed up by optimizing efforts to strengthen the integration of local potential in biology through appropriate learning strategies.